A review on application of Unmanned Aerial Vehicle (UAV) in agriculture / Saiful Nizar Abd Razak - Abd Razak, Saiful Nizar (Faculty of Plantation and Agrotechnology, 2019)
In this advanced era of technology, there are many machines or engineering tools that are being applied in many sectors in this world especially in agriculture to ease the job that had been done. For example, the uses of drone or unmanned aerial vehicles (UAV) in agricultural sector were widely used for many purposes that can greatly benefits the farmers and plantation companies. UAV is an aircraft attached or equipped with the sensors, processing unit and communication system that are not driven as human pilot but with auto control. There are many benefits of the drone or UAV that can easier the farmer’s job such as can be a method to control the pest and disease through spraying with the available of tank and nozzle as tool to spraying. Compared to the manual spraying, this method is quite effective and efficient because can cut cost and done in short period of time. The UAV also can be used as tool of crop monitoring especially for yield, weed and also pest and disease with the use of Normalized Difference Vegetation Index (NDVI). It is also can be used for mapping such as yield mapping and boundary mapping. Other than that, it is also can be used to improve the soil sampling. These have shown that the UAV can help the farmers and agriculture based company to make quick and accurate decision to overcome any problem occurred through the precise information.